Relevansi Konsep Multiple Intelligences, Spiritual Quotient, dan Adversity Quotient dalam Konteks Pengembangan Potensi Manusia terhadap Pendidikan Islam - Putra, Rudi Yongki Nanda; Wince, Wince; Fitriani, Wahidah (YASIN, 2025)
Although the development of human potential in education has been widely studied, research that specifically integrates the concepts of Multiple Intelligences, Spiritual Quotient, and Adversity Quotient within the context of Islamic education remains limited and tends to be partial. This study aimed to analyze the relevance and integration of these three concepts in developing human potential in Islamic education. It employed a qualitative approach with an analytical–critical literature study design. Data sources were obtained from nationally accredited journals and reputable international journals, academic books, and relevant scientific documents published within the last 5–10 years, selected using purposive sampling techniques. Data were collected using a document review instrument and analyzed through critical thematic analysis. The findings indicate that Multiple Intelligences is relevant for accommodating the diversity of learners’ potentials and fitrah, Spiritual Quotient functions as the foundational value system and transcendental orientation of Islamic education, and Adversity Quotient plays an important role in shaping learners’ resilience and perseverance in facing learning and life challenges (Gardner, 2018; Zohar & Marshall, 2019; Stoltz, 2017). These results contribute to the development of Islamic education theory by proposing an integrative conceptual framework that holistically links intellectual intelligence, spirituality, and psychological resilience (Muhaimin, 2020; Suyadi, 2020). The study concludes that integrating these three concepts in Islamic education is essential for forming intelligent, virtuous, and resilient individuals. The implications of this research include theoretical contributions to enriching the literature on Islamic education and practical implications for educators and administrators of Islamic educational institutions in designing holistic, value-oriented learning, as well as opening opportunities for further empirical studies to examine the implementation of this integrative framework in Islamic educational practice.